Method for creating high-value supercapacitor carbon nanoelectrode material by taking waste chromium scraps as raw material

By preparing layered porous carbon nanoelectrode materials from leather solid waste chromium chips, combined with metal polyphenol networks, the problem of limited specific capacitance of supercapacitor materials and waste treatment in leather industry is solved, and efficient and environmentally friendly supercapacitor electrode materials are achieved , improving energy storage performance and environmental sustainability.

CN119314808APending Publication Date: 2025-01-14FUZHOU UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411271101.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-11
Publication Date
2025-01-14

AI Technical Summary

Technical Problem

The existing supercapacitor materials have problems such as limited capacitance, poor rate performance and low conductivity. In addition, waste chromium chip treatment in the leather industry has high costs and environmental risks, so the waste utilization rate needs to be improved.

Method used

Using tannin solid waste waste chromium chips as raw materials, layered porous high-value carbon nanoelectrode materials are prepared through hydrolysis, ultrasonic treatment, crosslinking and high-temperature pyrolysis, combining tannin acid and MnSO4 to form a metal polyphenol network for use in Supercapacitor electrode.

Benefits of technology

Electrode materials with high specific capacity, excellent conductivity and long-term cycle life have been achieved, reducing preparation costs and reducing environmental pollution, demonstrating application potential in supercapacitors.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119314808A_ABST
    Figure CN119314808A_ABST
Patent Text Reader

Abstract

The invention discloses a method for creating a layered porous high-value carbon nanoelectrode material by taking waste chromium scraps as a raw material and application of the layered porous high-value carbon nanoelectrode material to a supercapacitor, and belongs to the technical field of supercapacitor energy storage material preparation. The material of the electrode is Cr-Mn (at) CCF-TA. In a carbon nanoelectrode material, the number of pores, discontinuity of conductive channels and oxygen-containing functional groups can influence the power density of the supercapacitor, and in order to further improve the performance of the carbon-based supercapacitor, a strategy of introducing metal heteroatoms on a waste chromium scrap base material through the interface modification effect of metal polyphenol supramolecules is adopted. Waste chromium scraps are used as a carbon source and a template, tannic acid modified waste leather collagen fibers are used for chelating metal manganese ions, then carbonization is carried out, and the layered porous Cr-Mn-coated CCF-TA carbon nanoelectrode material is successfully prepared and applied to a supercapacitor. The preparation method is simple in operation process, energy-saving and environment-friendly, and the obtained carbon nanoelectrode material has relatively high specific capacitance, relatively long cycle life and good tolerance under extreme conditions, which indicates that the carbon nanoelectrode material is a supercapacitor electrode material which has a good prospect and is low in cost and high in efficiency.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of supercapacitors, and specifically to a method for creating layered porous high-value carbon nano-electrode materials based on chromium-containing leather residues from leather making solid waste as raw materials, and the application of the materials in supercapacitors. Background Art

[0002] In response to the energy and environmental crisis, the development of efficient energy storage devices has become increasingly important. Supercapacitors, as one of the most promising alternatives in energy storage systems, are considered to be one of the most environmentally friendly devices due to their high power density, long-term stability, and rapid charging and discharging capabilities. The energy storage of supercapacitors is based on two principles: double-layer capacitance and pseudocapacitance. Although carbon-based double-layer capacitors have high power density and good cycle stability, their energy density is also low due to the limited specific capacitance of carbon materials. In comparison, pseudocapacitive materials, such as transition metal oxides and hydroxides, can provide higher specific capacitance. However, most pseudocapacitive materials have problems with poor rate performance and low conductivity. Therefore, a common method to improve the performance of supercapacitors is to use composite materials of pseudocapacitive materials and carbon materials as electrodes.

[0003] Tannin is a class of naturally occurring polyphenol compounds that are widely found in plants, especially in bark, peel and tea. Tannin has a polyphenol structure and provides abundant phenolic hydroxyl groups, which can form stable coordination complexes with metal ions. The metal polyphenol system forms a new type of composite electrode material by combining metal ions with polyphenol compounds and then loading them onto carbon materials. This material not only improves the conductivity and electrochemical activity of supercapacitors, but also enhances their stability and cycle life, showing great potential in the field of efficient energy storage. In the future, with the continuous improvement of preparation technology and the development of new polyphenol compounds, the application prospects of metal polyphenol systems in supercapacitors will be broader.

[0004] Waste chrome chips mainly come from the leather processing industry, especially the waste generated during the chrome tanning process. These wastes contain a large amount of trivalent chromium and hexavalent chromium, which are potentially harmful to the environment and human health. Currently, the commonly used treatment methods include landfill, incineration and chemical treatment, but these methods have high costs, secondary pollution and environmental risks. How to improve the utilization rate of leather waste has become an urgent problem to be solved in the current leather industry. Waste chrome chips contain a large amount of collagen fibers and chromium elements. We can fully utilize these resources to reduce pollution to the environment and promote sustainable development. Summary of the invention

[0005] The purpose of the present invention is to provide a method for creating a layered porous high-value carbon nano-electrode material using tanning solid waste waste chromium chips as raw materials and its application in supercapacitors.

[0006] To achieve the above object, the present invention provides the following technical solutions:

[0007] A method for creating a layered porous high-value carbon nano-electrode material using waste chromium chips as raw materials and its application in supercapacitors, comprising the following steps:

[0008] Step 1: Weigh a certain amount of waste chromium chips, put them into a beaker, add potassium hydroxide solution, stir them on a magnetic stirrer to fully hydrolyze, and then dry them to form collagen;

[0009] Step 2: Weigh a certain amount of tannic acid and MnSO4·H2O, dissolve them in deionized water respectively, and after ultrasonic treatment, perform ultrasonic mixing to obtain a metal polyphenol network precursor solution constructed by tannic acid;

[0010] Step 3: pouring the collagen hydrolyzed from the waste chromium chips in step 1 into the solution in step 2, adding a certain volume fraction of glutaraldehyde as a cross-linking agent, magnetically stirring at a certain temperature, then adding a certain amount of hydrochloric acid solution to adjust the pH to a certain value, and then continuing to magnetically stir for a certain time;

[0011] Step 4: Wash the product of step 3 with deionized water and anhydrous ethanol for 2 to 3 times, filter and dry the product in an oven to obtain Mn-TA@Cr-CF;

[0012] Step 5: Place the dried precursor product in a tube furnace in a nitrogen atmosphere for high-temperature pyrolysis, and cool it naturally to room temperature to obtain Cr-Mn@C CF-TA .

[0013] As a preferred embodiment, in step 1, the potassium hydroxide solution is 0.5 mol / L, the temperature of the magnetic stirrer is set to 80° C., the rotation speed is 600 rpm, and the stirring time is 8 h.

[0014] As a preferred solution, in step 2, the mass ratio of tannic acid to MnSO4·H2O is 1:1, and the time required for ultrasonication is 20 minutes.

[0015] As a preferred solution, in step three, 15 ml of 15% glutaraldehyde is added, the magnetic stirring time is 1 hour, the temperature is 60°C, the concentration of the hydrochloric acid solution is 0.5M, the pH value is adjusted to 7, and the subsequent magnetic stirring temperature is also 60°C for 2 hours.

[0016] As a preferred solution, in step 4, the drying temperature is 60° C. and the drying time is 24 hours.

[0017] As a preferred solution, in step five, in a pure nitrogen atmosphere, the temperature is raised to 50°C at a heating rate of 5°C / min and stabilized for 30 minutes, then the temperature is raised to 800°C at a heating rate of 5°C / min and maintained for 2 hours, and finally cooled to room temperature.

[0018] Technical advantages and beneficial effects of the present invention:

[0019] 1. The present invention adopts a simple and convenient synthesis method, which is economical, efficient, green and environmentally friendly. The synthesis steps are simple to operate, the reaction conditions are mild and easy to control, and the preparation cost is low;

[0020] 2. In 6M KOH electrolyte, the Cr-Mn@C obtained by the present invention has a larger metal oxide ratio and higher conductivity. CF-TA The electrode exhibits excellent specific capacity: the specific capacity value is 344F / g at a current density of 1A / g. CF-TA The electrode exhibited an excellent long-term cycle life and high reversibility during the entire cycle at a current density of 10 A / g; after 4000 charge-discharge cycles, its specific capacitance still retained 74% of its initial value; therefore, Cr-Mn@C CF-TA The material can be used as an electrode material in supercapacitors. BRIEF DESCRIPTION OF THE DRAWINGS

[0021] Figure 1 It is Cr 0.5 -Mn 0.5 @C CF-TA SEM images of nanocomposites;

[0022] Figure 2 Cr at different calcination temperatures 0.5 -Mn 0.5 @C CF-TA XRD patterns of nanocomposites;

[0023] Figure 3 It is Cr 0.5 -Mn 0.5 @C CF-TA XPS analysis of nanocomposites;

[0024] Figure 4 (ac) is Cr 0.5 -Mn 0.5 @C CF-TA Cyclic voltammetry characteristic curves of nano-electrode materials at calcination temperatures of 700°C, 800°C, and 900°C (test voltage scanning range: 0-0.5V, scanning speed: 10-50mV / s); Figure 4 d is the CV graph of waste chromium chips and different contents of manganese at a scanning speed of 50mv / s

[0025] Figure 5 (ac) is Cr 0.5 -Mn 0.5 @C CF-TA The charge and discharge curves of nano-electrode materials at calcination temperatures of 700°C, 800°C, and 900°C (current density is 1-5A / g). Figure 5 d is the GCD curve of waste chromium chips and electrode materials calcined at 800°C with different contents of metallic manganese at a current density of 1A / g;

[0026] Figure 6 Cr at different calcination temperatures 0.5 -Mn 0.5 @C CF-TA Impedance plots of nanocomposites;

[0027] Figure 7 It is Cr 0.5 -Mn 0.5 @C CF-TA Cycling performance of the nanocomposite material after 4000 charge and discharge cycles at a current density of 10 A / g. DETAILED DESCRIPTION

[0028] In order to make the purpose, technical solution and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not intended to limit the present invention.

[0029] In order to better understand the above technical solution, the above technical solution will be described in detail below in conjunction with the accompanying drawings and specific implementation methods.

[0030] The embodiment of the present invention provides a method for creating a layered porous high-value carbon nano-electrode material using waste chromium chips as raw materials and its application in supercapacitors, comprising the following steps:

[0031] Step 1: Weigh a certain amount of waste chromium chips, put them into a beaker, add potassium hydroxide solution, stir on a magnetic stirrer to fully hydrolyze, and then dry to form collagen. The potassium hydroxide solution is 0.5 mol / L, the temperature of the magnetic stirrer is set to 80°C, the speed is 600 rpm, and the stirring time is 8 hours;

[0032] Step 2: Weigh a certain amount of tannic acid and MnSO4·H2O, dissolve them in deionized water, and then perform ultrasonic mixing after ultrasonic treatment to obtain a metal polyphenol network precursor solution constructed by tannic acid. The mass ratio of tannic acid to MnSO4·H2O is 1:1, and the ultrasonic time is 20 minutes;

[0033] Step 3: Pour the collagen hydrolyzed from the waste chromium chips in step 1 into the solution in step 2, add a certain volume fraction of glutaraldehyde as a cross-linking agent, perform magnetic stirring at a certain temperature, then add a certain amount of hydrochloric acid solution to adjust the pH to a certain value, and then continue to perform magnetic stirring for a certain time. Among them, add 15ml of 15% glutaraldehyde, the magnetic stirring time is 1h, the temperature is 60℃, the concentration of the hydrochloric acid solution is 0.5M, the pH value is adjusted to 7, and the subsequent magnetic stirring temperature is also 60℃, and the time is 2h;

[0034] Step 4: Wash the product of step 3 with deionized water and anhydrous ethanol for 2 to 3 times, filter and put the product into an oven for drying to obtain Mn-TA@Cr-CF. The drying temperature is 60°C and the drying time is 24 hours;

[0035] Step 5: Place the dried precursor product in a tube furnace in a nitrogen atmosphere for high-temperature pyrolysis, and cool it naturally to room temperature to obtain Cr-Mn@C CF-TA The specific operation of high temperature pyrolysis is as follows: in a pure nitrogen atmosphere, the temperature is raised to 50°C at a heating rate of 5°C / min and stabilized for 30 minutes, then the temperature is raised to 800°C at a heating rate of 5°C / min and maintained for 2 hours, and finally cooled to room temperature;

[0036] The active material of the present invention is abbreviated as Cr-Mn@C CF-TA .

[0037] The present invention uses a platinum sheet as a counter electrode, a Hg / HgO electrode as a reference electrode, and the prepared electrode as a working electrode.

[0038] The present invention is further described below in conjunction with specific examples. In order to further understand the present invention, preferred embodiments of the present invention are described in conjunction with examples, but it should be understood that these descriptions are only for further illustrating the features and advantages of the present invention, rather than limiting the claims of the present invention. In addition, it should be understood that after reading the contents disclosed in the present invention, those skilled in the art may make various changes or modifications to the present invention, and these equivalent forms also fall within the scope of protection defined by the present invention.

[0039] Unless otherwise specified, the experimental methods used in the following examples are all conventional methods; the reagents, materials, etc. used in the following examples, unless otherwise specified, can be obtained from commercial channels.

[0040] Embodiment 1:

[0041] This embodiment demonstrates a method for creating layered porous high-value carbon nano-electrode materials using waste chromium chips as raw materials and its application in supercapacitors.

[0042] (1) Weigh 0.5 g of waste chromium chips, dissolve it in 25 ml of 0.5 mol / l potassium hydroxide solution, stir it on a magnetic stirrer for sufficient hydrolysis, set the temperature to 80° C., the speed to 600 rpm, and the time to 8 h, and then dry it to form collagen;

[0043] (2) Weighing 0.5 g of tannic acid and 0.5 g of MnSO4·H2O, respectively dissolving them in 30 ml of deionized water, and ultrasonically treating them for 20 min, and then ultrasonically mixing them to obtain a metal polyphenol network precursor solution constructed by tannic acid;

[0044] (3) Pour the collagen hydrolyzed from the waste chromium chips in step 1 into the solution in step 2, and add 15 ml of 15% glutaraldehyde as a cross-linking agent, and stir magnetically at 60° C. for 1 h, then add 0.5 M hydrochloric acid solution to adjust the pH to 7, and then continue to stir magnetically for a certain period of time, the stirring time is 2 h, and the temperature is 60° C.;

[0045] (4) washing the product of step 3 with deionized water and anhydrous ethanol for 2 to 3 times, filtering the product and drying it in an oven at 60° C. for 24 h to obtain Mn-TA@Cr-CF;

[0046] (5) The dried precursor product was placed in a nitrogen atmosphere and heated to 50°C at a heating rate of 5°C / min for 30 min. Then, the temperature was raised to 800°C at a heating rate of 5°C / min and maintained for 2 hours. The product was naturally cooled to room temperature to obtain Cr-Mn@C CF-TA ;

[0047] The Cr obtained in this example 0.5- Mn 0.5 @C CF-TA Phase identification, micromorphology and structure characterization of materials: Use XPS analyzer and XRD to identify the phase of the prepared materials, and use scanning electron microscope to characterize the micromorphology and structure of the obtained materials.

[0048] Figure 1 It is Cr 0.5 -Mn 0.5 @C CF-TA Scanning electron microscope image of the nanocomposite material. As can be seen from the image, the material has some long curved shapes, which is caused by the large amount of collagen fibers contained in the waste chromium chips. Not only that, we can also see that the material has many pores, which can provide more active sites, thereby increasing the charge storage capacity of the capacitor.

[0049] Figure 2 It is Cr 0.5 -Mn 0.5 @C CF-TAXRD patterns of nanocomposites at different temperatures (700°C, 800°C, 900°C). As can be seen from the figure, the purity of the obtained samples is relatively high, no obvious impurities are generated, and the sharper diffraction peaks indicate that the synthesized material has good crystallinity. The material has five obvious diffraction peaks at 2θ=34.303°, 49.296°, 58.559°, 61.383°, and 72.286°, which correspond to the (200), (220), (311), (222), (400), and (711) crystal planes of Mn+2S (PDF#06-0518). Obvious diffraction peaks appeared at 2θ=34.925°, 40.547°, 58.685°, 70.145°, and 73.763°, corresponding to the (111), (200), (220), (311), and (222) crystal planes of MnO (PDF#75-1090).

[0050] Figure 3 It is Cr 0.5 -Mn 0.5 @C CF-TA XPS graph of nanocomposite materials. As can be seen from the figure, the surface elemental composition of the material is further confirmed. Among them, (a) is the XPS full spectrum analysis graph of the nanocomposite material, which confirms the presence of five elements, namely C, O, Cr, Mn, and S, on the surface of the material. It can be seen from the C1S spectrum that it is mainly divided into three peaks, corresponding to the two sharp peaks of C=N (286.45eV) bond and sp2 C–C (284.8eV), and the broad peak of C=O (289.23eV) bond. The CC absorption peak shows that the composite material has a carbon matrix of graphitized carbon with good conductivity. The O1S spectrum shows two well-resolved peaks, with the oxygen-containing functional group OC (532.23eV) and Mn-O (530.3eV). This is consistent with the analysis results of XRD. It can be seen from the elemental spectrum of Cr 2p that the Cr element mainly exists in the form of +3 valence and +6 valence. In the high-resolution Mn2p spectrum ( Figure 3 -e) It can be seen that it is formed by four obvious peak fittings. The peaks at 653.96eV and 642.53eV correspond to Mn 2p1 / 2 and Mn 2p3 / 2 of divalent manganese, respectively, and the other two peaks correspond to tetravalent manganese. From the high-resolution S2p spectrum, it can be seen that there are three characteristic peaks, among which the characteristic peaks at 171.43eV and 164.67eV correspond to S2p1 / 2, and the characteristic peak at 169.13eV corresponds to S2p3 / 2.

[0051] Embodiment 2:

[0052] This example demonstrates the electrochemical performance of a supercapacitor made of layered porous high-value carbon nano-electrode materials using waste chromium chips as raw materials.

[0053] The composite carbon nanomaterial, acetylene black and polytetrafluoroethylene are mixed, anhydrous ethanol is added and ground to obtain a uniform black slurry, which is evenly coated on the nickel foam, dried and pressed by a tablet press to obtain a working electrode;

[0054] The mass ratio of the composite carbon nanomaterial, acetylene black and polytetrafluoroethylene is 8:1:1, and the active material loading of a single electrode is about 2-3 mg;

[0055] Cr-Mn@C CF-TA The electrochemical performance test of the composite carbon nanomaterial was carried out under a three-electrode system: the prepared electrode was used as the working electrode, the platinum electrode was used as the counter electrode, the Hg / HgO electrode was used as the reference electrode, and the KOH aqueous solution with a concentration of 6 mol / L was used as the electrolyte. The performance was evaluated by cyclic voltammetry test (CV), constant current charge and discharge test (GCD), AC impedance performance test and cycle life test.

[0056] Figure 4 Cr-Mn@C CF-TA CV diagrams at different calcination temperatures and different ratios, where Figure 4 a is 700℃, Figure 4 b is 800℃, Figure 4 c is 900℃, Figure 4 d is the CV diagram of different Mn contents at 800℃. The cyclic voltammetry test (CV) was carried out in the corresponding potential range (0-0.5V). Figure 4 (ac) is tested at different scan rates (10-50mv / s), from which the redox peak can be clearly observed. The shape of the CV curve shows that its capacitance characteristics are different from the double-layer capacitance, and the area of ​​CV also increases with the increase of the scan rate. At 800℃, the area of ​​its CV curve is larger than that of other temperatures. In addition, at 800℃, the CV curve with a scan rate of 50mV / s has a certain degree of deformation. This is due to the existence of internal active sites, and there has been a certain deformation and a decrease in specific capacitance, which cannot completely maintain the redox transition. Figure 4 d is the CV graph of different Mn contents measured at a scanning speed of 50 mv / s. It can be seen that when the Mn content is 0.5 g, the area of ​​the corresponding CV curve is the largest and its corresponding specific capacitance is also the largest.

[0057] Figure 5 (ac) is Cr 0.5- Mn 0.5 @C CF-TA GCD diagram of the electrode prepared at different calcination temperatures of the composite material, where Figure 5 a is 700℃, Figure 5b is 800℃, Figure 5 c is 900℃, Figure 5 d is the GCD diagram of waste chromium chips with different Mn contents at calcination temperature of 800℃. It can be seen that all curves show nonlinear charge and discharge curves, which further confirms the behavior of pseudocapacitance; these approximately symmetrical curves show that Cr-Mn@C CF-TA The electrode made of the composite material has excellent electrochemical capacitance properties.

[0058] The specific capacitance of the discharge curve is calculated according to the following equation (2):

[0059] C=IΔt / ΔVm eqn

[0060] C (F / g): specific capacitance; I (A): current; ΔV (V): discharge voltage difference; Δt (s): discharge time; m (g): mass of active material in the electrode;

[0061] By calculation, Cr-Mn@C CF-TA When the Mn content of the electrode material made of the composite material is 0.5g, the specific capacitance at the calcination temperature of 800℃ is the largest, and the high specific capacitance reaches 344F / g at the current density of 1A / g, while the specific capacitance at 700℃ is 172F / g, and the specific capacitance at 900℃ is 128F / g. It is worth noting that with the increase of current density, the specific capacity gradually decreases, which is mainly related to the reduction of ions and surface area at high charge and discharge current density.

[0062] Figure 6 The composite materials at different temperatures are shown in 10 -2 Up to 10 5 The impedance diagram recorded in the frequency range of Hz. The electrochemical impedance spectroscopy (EIS) test was carried out under open circuit potential conditions; the EIS curves of the three electrodes are composed of the high frequency region (charge transfer resistance, R ct ) and a 45-degree inclined linear part in the low-frequency region (Warburg resistance, Zw). The intersection of the curve and the x-axis represents the internal resistance (R0), which includes the contact resistance, ionic resistance and intrinsic resistance of the electrode material. It can be seen from the fitting analysis that the electrode at 800°C has the smallest R ct , indicating that its charge transfer resistance is small. Although its R0 is not the smallest, it is not much different from other temperature values. In the low frequency region, the slope of the straight line of the 800℃ electrode is the largest, reflecting its better charge transfer kinetics and explaining its superior ionic conductivity.

[0063] Figure 7 It is Cr 0.5 -Mn 0.5 @C CF-TAThe cycle performance diagram of the electrode made of the composite material after 4000 cycles at a current density of 10 A / g shows that after 4000 charge and discharge cycles, the capacitance retention rate is 74.2%, which indicates that the composite material has better cycle stability.

[0064] Although the embodiments of the present invention have been explicitly described, it will be understood by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and the scope of the present invention is defined by the appended claims and their equivalents.

Claims

1. A method for preparing layered porous high-value supercapacitor carbon nanoelectrode materials using waste chromium chips as raw materials, characterized in that: The preparation method comprises the following steps: Step 1: Weigh a certain amount of waste chromium chips and place them in a beaker, add potassium hydroxide solution into it, stir on a magnetic stirrer until fully hydrolyzed, and then dry to obtain chromium-containing collagen; Step 2: Weigh a certain amount of tannic acid and MnSO4·H2O, dissolve them in deionized water respectively, and after ultrasonic treatment, fully mix them to obtain a metal polyphenol network precursor solution constructed by tannic acid; Step 3: pouring the collagen hydrolyzed from the waste chromium chips in step 1 into the metal polyphenol solution in step 2, adding a certain volume fraction of glutaraldehyde as a cross-linking agent, magnetically stirring at a certain temperature, then adding a certain amount of hydrochloric acid solution to adjust the pH to a certain value, and then continuing to magnetically stir for a certain time; Step 4: Wash the product of step 3 with deionized water and anhydrous ethanol for 2 to 3 times, filter and dry the product in an oven to obtain a Mn-TA@Cr-CF precursor material; Step 5: Place the dried precursor product in a tube furnace in a nitrogen atmosphere for high-temperature pyrolysis, and cool it naturally to room temperature to obtain a hierarchical porous fiber-like Cr-Mn@C CF-TA Carbon nanoelectrode materials.

2. The preparation method according to claim 1, characterized in that: The potassium hydroxide solution in step 1 is 0.5 mol / L, the temperature of the magnetic stirrer is set to 80° C., the rotation speed is 600 rpm, and the stirring time is 8 h.

3. The preparation method according to claim 1, characterized in that: In the step 2, the mass ratio of tannic acid to MnSO4·H2O is 1:1, and the time required for ultrasonication is 20 minutes.

4. The preparation method according to claim 1, characterized in that: In the step 3, 15 ml of 15% glutaraldehyde was added, the magnetic stirring time was 1 hour, the temperature was 60° C., the concentration of the hydrochloric acid solution was 0.5 M, the pH value was adjusted to 7, and the subsequent magnetic stirring temperature was also 60° C. for 2 hours.

5. The preparation method according to claim 1, characterized in that: In the step 4, the drying temperature is 60° C. and the drying time is 24 hours.

6. The preparation method according to claim 1, characterized in that: In the step 5, under a pure nitrogen atmosphere, the temperature is raised to 50° C. at a heating rate of 5° C. / min and stabilized for 30 minutes, then the temperature is raised to 800° C. at a heating rate of 5° C. / min and maintained for 2 hours, and finally cooled to room temperature.

7. A method for producing a layered porous high-value carbon nano-electrode material using waste chromium chips obtained by the preparation method according to any one of claims 1 to 6 as raw materials.

8. Use of the waste chromium chips as claimed in claim 7 as raw materials to create layered porous high-value carbon nano-electrode materials in the preparation of supercapacitors.